Book Review: Leadership and Sustainability in the Built Environment (Construction Economics and Building, 2015)
Leadership and Sustainability in the Built EnvironmentOpoku, A. and Ahmed, V. (ed.), 2015. Leadership and Sustainability in the Built Environment. Routledge, London. ISBN (hbk): 978-1-13-877842-9, Hardback: $155.00.